PEMBELAJARAN KETERAMPILAN BERBAHASA ARAB KOMUNIKATIF INTERAKTIF PADA PEMBELAJARAN KITAB KUNING DI PESANTREN KHUSUS AL-HALIMY SESELA - Ahmad Helwani Syafi’I; Husnan; Abdu Rabbi Faqihuddin (Cordova Journal : languages and culture studies, 2022)
This study discusses interactive communicative learning of Arabic language skills in the study of the yellow book at the Al-Halimy Sesela Special Islamic Boarding School. In this study, we want to reveal how the process of teaching and learning to speak Arabic based on interactive communication in the yellow book learning frame and what obstacles students face. This research uses a qualitative approach in the process of collecting data from the field. The data collection techniques are carried out by means of observation, interviews, and documentation. The results of research conducted at the Al-Halimy Islamic boarding school specifically for boys found a form of activity that supports the improvement of students' Arabic speaking skills by providing material for strengthening Arabic such as vocabulary (mufradat), imla' and nahu and shraf, and using methods varied according to the material being taught. The yellow book as a basis for learning there greatly influences the speaking skills of students, besides that, we cannot ignore the milieu which has an important role in the Islamic boarding school environment.